Desenvolvimento e caracterização de novos materiais destinados à liberação modificada de ativos farmacoterapêuticos - Sgorla, Débora (2017)
Introduction: Progress in the release of pharmacotherapeutic agents and improved quality of life for patients depends on the development of novel and suitable drug delivery systems because a number of conventional pharmaceutical forms can trigger multiple side effects as well as inconvenient administrations, which ultimately lead to poor treatment adhesions or inefficient treatments. Objectives: To develop new materials for application in modified drug release systems, whose potential uses are for coating solid oral dosage forms and insulin encapsulation for oral administration. Methodology: Coating films: Initially, hyaluronic acid was crosslinked with trisodium trimetaphosphate in aqueous alkaline media. Afterwards, the films were produced by evaporation method by incorporation of the unmodified and crosslinked biopolymer into the ethylcellulose dispersion in different proportions. The obtained films were characterized by morphology by scanning electron microscopy, robustness to water vapor permeability and hydration capacity in physiological simulation fluids. In addition, safety and biocompatibility were evaluated against Caco-2 and HT29-MTX intestinal cells. Lipid-polymeric nanoparticles: They were produced from the association of ethylpalmitate and HPMC-AS, through the modified solvent emulsification-evaporation technique by sonication. Subsequently, the nanoparticles were characterized by size, polydispersity index, zeta potential and encapsulation efficiency, besides morphology by scanning electron microscopy, X-ray diffraction and thermal analysis. It was also evaluated the in vitro release profile, as well as insulin uptake in a triple co-culture model, and safety and biocompatibility against Caco-2 and HT29-MTX intestinal cells. Results: Coating films: The permeability to water vapor was influenced by the increase of hyaluronic acid content in the final formulation. When immersed in gastric simulation fluid, the films presented lower swelling compared to greater hydration in intestinal simulation fluid. Simultaneously, in intestinal simulation fluid, they presented mass loss, revealing the ability to prevent premature drug release at gastric pH, yet vulnerable to release into the intestinal environment. In addition to these results, the physico-chemical characterization suggested thermal stability of the films and physical interaction between the constituents of the formulation. Finally, cytotoxicity tests demonstrated viii that both membranes and individual materials were safe for intestinal cells when incubated for 4 h. Lipid-polymer nanoparticles: The suggested methodology yielded nanoparticles with satisfactory mean size, 297.57nm ± 29.99, PDI of 0.247 ± 0.03 and zeta potential of -19.13 ± 5.88. In addition, high encapsulation efficiency was achieved, around 83.92 ± 4.32% and DSC showed an improvement in the thermal stability of the formulation compared to individual materials. This is demonstrated by endothermic peaks of degradation that decreased in intensity and moved to higher temperatures. DRX results showed alteration of the crystalline state to amorphous, inferring the drug incorporation. The cumulative release demonstrated that only 9.0% of the encapsulated insulin was released after 2 h, reaching approximately 14% after 6h. These results altered the permeability of insulin through in vitro intestinal model. Regarding the biocompatibility with Caco-2 and HT29-MTX cells, lipid-polymeric nanoparticles did not show toxicity up to 4 hours. Conclusions: The results suggest that hyaluronic acid based films may prevent premature drug release under hostile conditions of the stomach but control the release in the more distal portions of the gastrointestinal tract when applied as coating material in solid oral dosage forms. Furthermore, they were safe to intestinal mucosa. Regarding the lipid-polymeric nanoparticles, evidences show that they can protect insulin from the hostile conditions found in the TGI, also guaranteeing the safety of the intestinal mucosa depending on its concentration. However, a better release profile and consequently better insulin uptake can be achieved by optimizing the proposed formulation.